Biology and Control of Ragweed Parthenium in Non-Cropland - Dennis C. Odero; Brent A. Sellers; Jason A. Ferrell (EDIS)
Ragweed parthenium is considered a noxious weed in many parts of the world because of its allelopathic effect on other plants and the health risks it poses to humans. It causes allergic contact dermatitis, rhinitis, and respiratory problems in sensitive humans. Learn more in this 3-page fact sheet written by D.C. Odero, B.A. Sellers, and J.A. Ferrell and published by the UF Department of Agronomy, April 2011.